Perancangan tas multifungsi untuk membantu penjualan UMKM Reka Heritage berbasis kulit nabati - Christabella, Valencia; Herdiana, Wyna; Hairunnas, Hairunnas (Institut Seni Indonesia Yogyakarta, 2024)
Vegetable tanned leather is a natural leather tanned using natural ingredients of the tree extracts. Vegetable tanned leather has a fairly high market demand because this leather does not use any chemicals so it tends to be environment-friendly, strong resistance, and cheaper price. Vegetable tanned leather is generally used as a basic material for fashion-based products, such as bag. Bag is generally used to carry various items needed when travelling. Moreover, bag has been one of the main indicators of creating a stylish look. The tendency to focus more on the physical appearance has changed the main function of bag itself. Many bags these days are not really efficiently made by having a small size as to make it look simple and stylish. In this research, the writer is accomodated by SME Reka Heritage which is located in Sidoardjo, East Java. The aim of the product design in this research is to help the SME providing new fashion-based product innovation. This product targets people in general, especially women by designing a multifunction, stylish, and efficient bag.